PENGARUH PEMBERIAN JUS BELIMBING MANIS TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PANTI WERDHA BINA BHAKTI SERPONG TAHUN 2018 - Riswahyuni Widhawati; Eka Indri Widiyastuti; Oryza Intan Suri (STIKes IMC Bintaro, 2020)
Hypertension is the increase in systolic blood pressure greater than 140 mmHg and a diastolic blood pressure of more than 90 mmHg the measurement on two occasions with an interval of five minutes in a State of rest or quiet enough. Hypertension disease can attack a wide range of ages, including the elderly. Sweet star fruit (Averrhoa Carambola linn) is one of the traditional medicine antihipertensi medication, potassium in star fruit sweet functioning lower blood pressure so as to prevent high blood pressure. Potassium is an important mineral for the mengintrol nerve and balance blood pressure. The purpose of this research is to know the influence of granting sweet star fruit juice against a decrease in blood pressure in people with hypertension in an Werdha Bina Bhakti Serpong. Type of this research is quantitative with the design of the experimental quasy pre and post test with non equivalent control group, conducted on 30 sufferers of hypertension. The results showed there was significant influence between blood pressure before and after the awarding of the star fruit juice sweetened with the results of the statistical tests using paired t-test of 0000 < 0.05. Recommendations on the research that is, in order for the sweet star fruit juice can be applied as a remedy in an nonfarmakologis Werdha Bina Bhakti Serpong to control hypertension.